Structured report for dynamic ultrasonography in patients with suspected or known endometriosis: Recommendations of the International Society for Gynecologic Endoscopy (ISGE) - Djokovic, Dusan; Pinto, Patrícia; van Herendael, Bruno J; Laganà, Antonio Simone; Thomas, Viju; Keckstein, Jörg (European journal of obstetrics, gynecology, and reproductive biology, 2021)
OBJECTIVE: The International Society for Gynecologic Endoscopy (ISGE) developed this project to establish the recommendations for structured reporting of dynamic ultrasound findings, promoting on this manner the practice of standardized, comprehensive and systematic evaluation and reporting of endometriosis in pelvic structures, in correlation with the #Enzian classification. STUDY DESIGN: A non-systematic review was done through a search on the following databases: MEDLINE, EMBASE, Global Health, The Cochrane Library (Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, Cochrane Methodology Register), Health Technology Assessment Database and Web of Science, using the medical subject heading (MeSH) term "endometriosis" (MeSH Unique ID: D004715) in combination with "diagnostic imaging" (MeSH Unique ID Q000000981) and "consensus" (MeSH Unique ID D032921). The information extracted from the articles of interest, written in English and published from inception of the above-mentioned databases until May 2021, was graded by the level of evidence using the American College of Chest Physicians (ACCP) classification system. The recommendations for a structured reporting of ultrasound findings were developed through multiple cycles of literature analysis and expert discussion following the Delphi method. RESULTS: The ISGE recommends the adoption of the terms, definitions and methods proposed by the International Deep Endometriosis Analysis (IDEA) Group for ultrasound assessment of patients with suspected or known endometriosis (grade 1C), since this is the most comprehensive and systematic concept currently available. This paper provides the ISGE structured reporting template for presenting quantitative and qualitative information upon the IDEA consensus-based sonographic assessment of the uterus, adnexa, anterior and posterior compartment. The #Enzian classification is recommended to summarize the findings in a standard fashion (grade 1B). CONCLUSION: Mapping of pelvic endometriosis by ultrasound is accurate when trained sonographers perform the technique. Structured reporting of the lesions may improve patient counseling and treatment planning, including the organization of multidisciplinary teams and the selection of the most appropriate medical or surgical therapeutic strategy.
Keywords: endoskopie; uterus; Uterus; endometrióza; Endometriosis; lidé; Female; Endoscopy; Structured report; Systematic Reviews as Topic; #Enzian; Classification system; Ultrasonography; ultrasonografie; systematický přehled jako téma; ženské pohlaví; Ultrasound; Humans